Influence of social media technologies on organizational performance through knowledge and innovation. Issue 3 (2nd July 2018) - Garcia-Morales, Victor Jesus; Martín-Rojas, Rodrigo; Lardón-López, María Esmeralda
Abstract : Purpose: The purpose of this paper is to show how social media technologies (SMT) make the firm proficient to act on business opportunities and reconfigure business resources by encouraging networks to routinize the firm's knowledge and innovation competencies. Design/methodology/approach: The paper analyzes data obtained from a sample of 201 technological firms located in Spain. Structural equation modeling with Lisrel is used to test the hypotheses. Findings: This paper contributes to the literature by reflecting empirically in a structural model how SMT drive technological knowledge competencies to improve organizational performance directly and indirectly by leveraging processes of innovation capability in the firm. Research limitations/implications: The study has some limitations, among them transversal analysis of different constructs. The number of relationships analyzed is limited, as is the literature focuses on a digital vision from a social media point of view. Practical implications: Some implications for managers emerge. SMT both enable an emergent participatory culture through ubiquitous digital devices and social networks and balance constant connectivity afforded by digital devices. Originality/value: Drawing on complexity science, the authors develop a conceptual framework to explain how social media, as emergent IS phenomena, help firms to create business value, leveraging network effects and knowledge flows, and increasing innovative capability.